Deciphering the guitar of João Gilberto in his arrangement of Desde que o samba é samba (2000) - Guilherme Silva Espindola; Bruno Madeira (Per Musi, 2023)
When we talk about João Gilberto we talk about arrangement, versions, recording, revisiting and a refreshing of many songs that were recorded during his career, songs that in most cases are not his original compositions. This paper presents an investigation of João Gilberto’s harmony in his recording of Desde que o samba é samba. This work was made possible through the audition, transcription and comparison of João’s guitar and the first recording of the cited song. The audition, being key to identify aspects of his ideas, the transcription brought us, with detail, each note played by him, and finally, the comparison, being the raw material for the paper, allowed the detailed exploration on the musical ideas behind the recording, bringing theories about João’s concepts on structure, arrangement, harmony and his main instrument, the guitar, being those elements that together characterize João’s style of interpretation and arrangement.